2005
DOI: 10.1073/pnas.0505266102
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide transcriptional analysis using Arabidopsis thaliana Affymetrix gene chips determined plant responses to phosphate deprivation

Abstract: Phosphorus, one of the essential elements for plants, is often a limiting nutrient because of its low availability and mobility in soils. Significant changes in plant morphology and biochemical processes are associated with phosphate (Pi) deficiency. However, the molecular bases of these responses to Pi deficiency are not thoroughly elucidated. Therefore, a comprehensive survey of global gene expression in response to Pi deprivation was done by using Arabidopsis thaliana whole genome Affymetrix gene chip (ATH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

84
955
9
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 816 publications
(1,056 citation statements)
references
References 36 publications
84
955
9
8
Order By: Relevance
“…Although PC is present in the outer membrane of the plastid envelope, the only known site of PC de novo biosynthesis is localised in the ER. A direct import of PC from ER, or an import of intermediates derived from endoplasmic reticulum PC, possibly DAG or phosphatidate, is therefore required for the synthesis of eukaryotic galactolipids However, the existence of a phospholipase D (PLDζ2) activated by phosphate deprivation [42,43], the accumulation of phosphatidate in the tgd1 mutant and the localization of TGD1 in the chloroplast inner envelope membrane [37] suggest that the transported molecule could be phosphatidate. To understand this latter scheme, the precise localization of the phosphatidic acid phosphatase (PAP) involved in the transformation of eukaryotic phosphatidate into DAG is crucial since part of the eukaryotic DAG is galactosylated by MGD1, the constitutive MGDG synthase that is present in the inner envelope membrane.…”
Section: Energy-dependent Translocasesmentioning
confidence: 99%
“…Although PC is present in the outer membrane of the plastid envelope, the only known site of PC de novo biosynthesis is localised in the ER. A direct import of PC from ER, or an import of intermediates derived from endoplasmic reticulum PC, possibly DAG or phosphatidate, is therefore required for the synthesis of eukaryotic galactolipids However, the existence of a phospholipase D (PLDζ2) activated by phosphate deprivation [42,43], the accumulation of phosphatidate in the tgd1 mutant and the localization of TGD1 in the chloroplast inner envelope membrane [37] suggest that the transported molecule could be phosphatidate. To understand this latter scheme, the precise localization of the phosphatidic acid phosphatase (PAP) involved in the transformation of eukaryotic phosphatidate into DAG is crucial since part of the eukaryotic DAG is galactosylated by MGD1, the constitutive MGDG synthase that is present in the inner envelope membrane.…”
Section: Energy-dependent Translocasesmentioning
confidence: 99%
“…Genome-wide transcriptional analyses showed that ALA10 transcription is upregulated under phosphate starvation 26 . We confirmed these data by quantitative real-time PCR, which demonstrated a highly reproducible 20% increase of ALA10 transcript levels under these conditions (Fig.…”
Section: Ala10 Internalizes Lysopc and Glycerophospholipids In Plantamentioning
confidence: 99%
“…The CDP-DAG pathway is more active in the growth phase but nutrient depletion induces a shift towards the Kennedy pathway [16]. The Kennedy pathway indeed contributes to recycling the polar head of phospholipids such as choline and ethanolamine [20] According to [21] Leaf Root Whole seedling ATS1 Glycerol-3-phosphate acyltransferase through phospholipases D (PLDs) and eventually to remodelling of membranes. The PA phosphatase Pah1p is critical for the shift from the CDP-DAG to the Kennedy pathway because it catalyzes the hydrolysis of PA into DAG, and furthermore because the Pah1p-produced DAG negatively regulates the level of expression of genes encoding the CDP-DAG pathway [16].…”
Section: Phosphatidic Acid As An Intermediate Metabolite In Galactolimentioning
confidence: 99%
“…However, it is likely important to distinguish two phases in the lipid response to Pi deprivation. In an early stage, a transient increase of PC precedes the increase of galactolipid synthesis [19] and several phospholipases D and C such as PLDz1, PLDz2, NPC4 and NPC5 are highly overexpressed [20,21]. Therefore, this suggests that, at this stage, the Kennedy pathway actively contributes to remodelling of phospholipids, notably of PE into PC [19].…”
Section: Phosphatidic Acid As An Intermediate Metabolite In Galactolimentioning
confidence: 99%
See 1 more Smart Citation